Improvement of the specific activity of the extracted mycelium-bound lipase of Aspergillus flavus - Mohd Danial, Azlina; Long, Kamariah; Mohd Ghazali, Hasanah (Malaysian Agricultural Research and Development Institute (MARDI), 2004)
Specific activity of lipase extracted from the mycelium of Aspergillus flavus, obtained from 3-day-old culture, increased nearly two times higher than from its culture supernatant. Different types of parameters were tested to optimise the extraction of mycelium-bound lipase. Highest specific activity of A. flavus lipase was obtained at 30 °C for 30 min with the agitation rate of 200 rev/min. Tris-HCl buffer (0.05 M) at pH 8.2 was the best extractant followed by Triton X-100 (0.1%), EDTA (0.01 M), NaCl (1 M) and Tween-80 (0.01%). The optimised conditions developed for the extraction of mycelium-bound lipase improved the purity of this lipase by 2.9 times higher than the control.